PENERAPAN KEMAMPUAN MOTORIK HALUS MELALUI TEKNIK MOZAIK DI KELOMPOK B TKIT BINA ILMU KECAMATAN SEKAMPUNG KABUPATEN LAMPUNG TIMUR - Revina Rizqiyani; Nurul Andini; Nihwan (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2023)
The application of fine motor skills is a good movement ability in children which is very necessary for early childhood development. Through mosaic activities in developing fine motor skills, children can begin to make simple hand movements and can coordinate hand muscles. This research aims to develop children's fine motor skills through the mosaic activity of sticking grains into a picture that has been prepared for children aged 5-6 years at the Bina Ilmu Integrated Islamic Kindergarten. The research method used was qualitative with the research subjects being group B children of the Bina Ilmu Integrated Islamic Kindergarten, Sekampung District with a total of 30 children consisting of fourteen children and six children with fine motor skills. Data collection used research, interviews and documentation followed by research results showing the development of fine motor skills through mosaic techniques such as. Thus, it can be concluded that the use of mosaics in developing children's fine motor skills develops optimally because teachers plan and prepare learning tools and materials before starting a lesson.